Properties of sodium methyl ester alpha-aulfo alkylate/trimethylammonium bromide mixtures - Chuah, C.H.; Wong, S.P.; Lim, W.H.; Cheng, S.F. (Springer Verlag, 2012)
The surface properties of binary mixtures of anionic sodium methyl ester α-sulfo alkylate (CmMES) and cationic alkyl trimethylammonium bromide (CⁿTAB) of different carbon chain length have been studied in the present work. The critical micelle concentration (CMC) that was obtained from the plots of surface tension (y) versus concentration showed that mixed surfactants have CMC values that were about 10 times lower than their single components.The large negative values for both interaction parameters suggest the existence of strong synergism between the oppositely charged surfactant molecules. The effect of hydrocarbon chain length of either surfactant was also compared and results showed that the effect of cationic surfactant chain length dominated that of the anionic surfactants. It was also discovered that certain mixed surfactant combinations behave differently from the expected trend.